Generalist Life Cycle Aids Persistence of Alexandrium ostenfeldii (Dinophyceae) in Seasonal Coastal Habitats of the Baltic Sea - Jerney, Jacqueline (J Phycol, 2019)
In seasonal environments, strong gradients of environmental parameters can shape life cycles of phytoplankton. Depending on the rate of environmental fluctuation, specialist or generalist strategies may be favored, potentially affecting life cycle transitions. The present study examined life cycle transitions of the toxin producing Baltic dinoflagellate Alexandrium ostenfeldii and their regulation by environmental factors (temperature and nutrients). This investigation aimed to determine whether genetic recombination of different strains is required for resting cyst formation and whether newly formed cysts are dormant. Field data (temperature and salinity) and sediment surface samples were collected from a site with recurrent blooms and germination and encystment experiments were conducted under controlled laboratory conditions. Results indicate a lack of seasonal germination pattern, set by an endogenous rhythm, as commonly found with other dinoflagellates from the Baltic Sea. Germination of quiescent cysts was triggered by temperatures exceeding 10°C and combined nutrient limitation of nitrogen and phosphorus or a drop in temperature from 16 to 10°C triggered encystment most efficiently. Genetic recombination was not mandatory for the formation of resting cysts, but supported higher numbers of resistant cysts and enhanced germination capacity after a resting period. Findings from this study confirm that A. ostenfeldii follows a generalist germination and cyst formation strategy, driven by strong seasonality, which may support its persistence and possibly expansion in marginal environments in the future, if higher temperatures facilitate a longer growth season.